Prospective observational study of oral clonazepam to prevent high-dose busulfan-induced seizures in adult patients - María Sacramento Díaz-Carrasco; Andrés Sánchez-Salinas; Juan José Fernández-Ávila; Raquel Olmos-Jiménez; Ignacio Español-Morales; Alberto Espuny-Miró (Journal of the Egyptian National Cancer Institute)
Abstract Background Busulfan at high doses has been associated with a risk of seizures. Phenytoin has been used traditionally as anti-seizure prophylaxis, and benzodiazepines and levetiracetam have been introduced more recently, providing data from retrospective series. The main purpose of this study was to evaluate the effectiveness of oral clonazepam as anti-seizure prophylaxis in adult patients receiving high doses of intravenous busulfan as part of the conditioning regimen for hematopoietic stem cell transplantation. The secondary objectives were to determine the feasibility of this regimen and to analyze the adverse events associated with the use of clonazepam. Methods This prospective, single-center study included 64 adult patients who received conditioning regimens with high doses of intravenous busulfan and anti-seizure prophylaxis with oral clonazepam, at a dose of 1 mg/8 h, from 12 h before starting treatment with busulfan until 48 h after ending administration. Results The effectiveness of the prophylaxis was 100%, with no episodes of seizures during busulfan treatment or in the 72 h afterwards. Treatment was feasible, and oral scheduled administration was completed in all patients. Adverse events that could be associated with clonazepam included the onset of somnolence, dizziness, and confusion, mostly mild. Conclusion The oral clonazepam regimen described in this study has been prospectively shown to be an effective, feasible anti-seizure prophylaxis option with manageable toxicity.